2015
DOI: 10.4331/wjbc.v6.i3.265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agitation speed on the morphology ofAspergillus nigerHFD5A-1 hyphae and its pectinase production in submerged fermentation

Abstract: AIM:To investigate the impact of agitation speed on pectinase production and morphological changing of Aspergillus niger (A. niger ) HFD5A-1 in submerged fermentation. METHODS:A. niger HFM5A-1 was isolated from a rotted pomelo. The inoculum preparation was performed by adding 5.0 mL of sterile distilled water containing 0.1% Tween 80 to a sporulated culture. Cultivation was carried out with inoculated 1 × 10 7 spores/mL suspension and incubated at 30 ℃ with different agitation speed for 6 d. The samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 14 publications
4
39
0
Order By: Relevance
“…After cultivation, a well grown mycelial film covered the surface of the cultivation medium in the static liquid system, while spherical pellets were present in the cultivation medium of the shaking system. It was noted that the cultivation system affects the morphological characteristics of the fungal hyphae/mycelia which is in accordance with the findings of Ibrahim et al (2015). The lovastatin concentrations produced in both systems are shown in Figure 1 as a function of cultivation time.…”
Section: Cultivation Systemsupporting
confidence: 86%
“…After cultivation, a well grown mycelial film covered the surface of the cultivation medium in the static liquid system, while spherical pellets were present in the cultivation medium of the shaking system. It was noted that the cultivation system affects the morphological characteristics of the fungal hyphae/mycelia which is in accordance with the findings of Ibrahim et al (2015). The lovastatin concentrations produced in both systems are shown in Figure 1 as a function of cultivation time.…”
Section: Cultivation Systemsupporting
confidence: 86%
“…Aeration provides good transfer of nutrients and product gases in the submerged fermentation system. Agitation speed and dissolved oxygen are important factors in determining the successful of microbial cultivation whereby the sufficient dissolved oxygen in growth medium is crucial in mass transfer characteristics of microbial cells (Ibrahim et al, 2015). The present study revealed that the static condition produced the highest anti-MRSA activity and the activity was decreased with the increment of agitation speeds.…”
Section: Discussionmentioning
confidence: 53%
“…The fungal growth was determined according to method described by Ibrahim et al, (2015) and the fungal cell dry weight was then expressed as g/L.…”
Section: Determination Of Fungal Growthmentioning
confidence: 99%
“…Microbiological research frequently involves cell culture experiments using chemically defined synthetic media in small flasks. In biotechnological research, the applicability of such laboratory generated data to industrial conditions is of primary importance (Farid et al , Ercan et al , Jayakar and Singhal , Saad et al , Ibrahim et al , Leite et al ). In wine microbiology, it has already been reported that several parameters influence the successful completion of the fermentation and the production of desirable flavour compounds.…”
Section: Introductionmentioning
confidence: 99%